2008
DOI: 10.1097/mlg.0b013e31815a9ed3
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Quality of Life After Total Laryngectomy and Postoperative Radiotherapy Versus Concurrent Chemoradiotherapy for Laryngeal Preservation

Abstract: We found better long-term QoL scores in patients undergoing concurrent chemoradiation. This appears to be mainly because of better physical functioning, social functioning, and social contact and smaller problems with pain, respiration, speech, the senses, and sleep disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 25 publications
3
92
2
1
Order By: Relevance
“…21 However, this group found chemoradiation to be superior in terms of global QOL, speech and social contact compared to those undergoing surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, this group found chemoradiation to be superior in terms of global QOL, speech and social contact compared to those undergoing surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients for whom the presence of a prescription for opioids indicated they had not stopped using opioids at 3 months after the completion of radiation therapy were considered to be "nonstoppers." The 3-month cutoff time was based on the findings of previous studies indicating that a majority of patients return to their baseline level of pain and function within 3 months after treatment [6,7,[22][23][24]. In addition, we also conducted an analysis of stoppers versus nonstoppers at the 6-month period to determine if identified risk factors at 3 months are persistent at 6 months, as well as to determine duration of treatment among those patients who ultimately succeeded becoming stoppers.…”
Section: Methodsmentioning
confidence: 99%
“…The only studies that examined voice self-assessment in relation with psychological states studied populations with severe voice disabilities and voice pathologies. They observed that negative voice self-assessment and speech in patients who suffered partial or total laryngectomies was associated with higher levels of depression and anxiety and withdrawal from social activities (Devins et al 1994;Nalbadian et al 2001;Birkhaug et al 2002;de Maddalena 2002;Hanna et al 2004;Boscolo-Rizzo et al 2008;Danker et al 2010). Our results demonstrate that the relationship between voice self-assessment and psychological states also holds in the normal population.…”
Section: Connected Speechmentioning
confidence: 99%